2020
DOI: 10.3390/v12030254
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Identification of Potential Vaccine Targets for the COVID-19 Coronavirus (SARS-CoV-2) Based on SARS-CoV Immunological Studies

Abstract: A.A.Q); m.mckay@ust.hk (M.R.M.) † These authors contributed equally to this work.Abstract: The beginning of 2020 has seen the emergence of COVID-19 outbreak caused by a novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). There is an imminent need to better understand this new virus and to develop ways to control its spread. In this study, we sought to gain insights for vaccine design against SARS-CoV-2 by considering the high genetic similarity between SARS-CoV-2 and SARS-CoV, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
899
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,053 publications
(972 citation statements)
references
References 50 publications
(75 reference statements)
25
899
0
18
Order By: Relevance
“…This shortlist of peptides is proposed by the authors for experimental validation. Another relevant paper was published by Ahmed et al [18], who combined experimental, in silico and populational approaches. Based on previous knowl-edge, the authors first identified experimentally determined SARS-CoV-1 derived T cell epitopes in the immunogenic structural spike (S) and nucleocapsid (N) proteins of SARS-CoV-1 that were associated with positive T cell or HLA binding assays, based on the high genetic similarity between the two viruses.…”
Section: Bioinformatic and Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This shortlist of peptides is proposed by the authors for experimental validation. Another relevant paper was published by Ahmed et al [18], who combined experimental, in silico and populational approaches. Based on previous knowl-edge, the authors first identified experimentally determined SARS-CoV-1 derived T cell epitopes in the immunogenic structural spike (S) and nucleocapsid (N) proteins of SARS-CoV-1 that were associated with positive T cell or HLA binding assays, based on the high genetic similarity between the two viruses.…”
Section: Bioinformatic and Experimental Studiesmentioning
confidence: 99%
“…Ahmed et al 2020 [18] SARS-CoV-2 Peptide-binding and immunogenetic predictions for SARS-CoV-2 derived peptides and population coverage analysis of the associated HLA alleles.…”
Section: Virus Bioinformatic Approach Experimental Approach Main Concmentioning
confidence: 99%
“…Specifically, we have extensively studied the free energies and dynamics of RBD-ACE2 binding, spike protein, and free RBD protein systems. Given that the spike protein is not only a potential drug target but also the virus antigen [35], the present study will be beneficial for the drug design, vaccine development, and disease prevention of SARS-CoV-2.…”
mentioning
confidence: 99%
“…At the same time, already at the preclinical level, the administered vaccines based on the administration of the entire SARS-CoV-2 spike protein ( (56)(57)(58) or on the administration of the single SARS-CoV-2 spike RBD, will induce the production of specific antibodies that might be sequenced and modelled in silico. On this concern, the provided molecular network will help in quantifying interactions between SARS-CoV-2 RBD (also in cases of different RBD variants (86)) and the newly investigated antibodies, i.e.lower the calculated binding energy in the modelled complex, higher the likelihood to have more success with the investigated vaccines/antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…understanding virus invasion mechanisms, developing new vaccines or antibodies, identifying small molecules with high affinity for viral proteins and establishing quick/safe diagnosis selective/specific kits. Indeed, the scientific community is now focused in the development of new weapons for containing SARS-CoV-2 spread and COVID-19 complications as it could be observed in the enormous effort in developing new vaccines based on a virus protein/nucleic acid portion able to induce an efficient and specific immunogenic response(56)(57)(58)(59)(60), or in developing a neutralizing antibody highly specific for SARS-CoV-2 spike RBD(25,26,(61)(62)(63)(64), or in identifying chemicals with high affinity for SARS-CoV-2 crucial proteins (1-3, 65-67).…”
mentioning
confidence: 99%